Influência do inóculo rala sobre as características físico-químicas, microbiológicas e reológicas do Queijo Minas Artesanal do Serro MG - Marcus Welbert Lempk (2018)
The use of natural lactic cultures or natural starter culture named "pingo" or fermented serum in the production of artisanal Minas cheese is mandatory for its legal recognition in the State of Minas Gerais. However there are no scientific studies that prove that the use of natural starter culture is necessary for the manufacture of these cheese. Many producers have been using the product named "rala" as a starter culture in the production of these cheese in substitution for the pingo. Thus it was aimed to make the comparison between the artisanal Minas-type cheese of the Serro - MG region, produced with and without rala as the natural starter culture, in order to verify the influence of their use on the physical-chemical, microbiological and rheological characteristics of produced cheese in two seasons of the year (rainy and dry) and during the maturation process. It was performed physical-chemical analysis (total dry extract, moisture, fat, pH, chlorides, water activity, fixed mineral residue, total protein, depth and extent of proteolysis); microbiological analysis (coliforms 30 ° C, Escherichia coli and Staphylococcus aureus) rheological (hardness, gumminess, cohesiveness, elasticity and chewing). The experiments were carried out three times in a randomized block design with a factorial scheme (maturation time x use or non-use of the natural starter culture and seasons of the year). The physical-chemical, microbiological and rheological results were submitted to regression analysis and the angular coefficients of the curves for each attribute were compared by analysis of variance (ANOVA). The averages of the results of the different treatments were compared by the Tukey test at 5% probability. For physical-chemical analysis the use or not of the rala did not cause significant effect capable of differentiating the cheese which were produced. The significant alterations occurred in the cheese were mainly due to the season and the time of maturation. Microbiologically, the use of the rala also had no significant influence on the counts of Coliformes 30º, E. coli and S. aureus. Regarding the texture profile, the use or not of rala caused significant difference only in the hardness, gumminess and chewing variables. The maturation time was the major responsible for the significant changes in the texture of the cheese.